Sources for sedimentary bacteriohopanepolyols as revealed by 16S rDNA stratigraphy - Coolen, Marco; Talbot, H.; Abbas, B.; Ward, C.; Schouten, S.; Volkman, J.; Damsté, J. (Wiley-Blackwell Publishing, 2008)
Bacteriohopanoids are widespread lipid biomarkers in the sedimentary record. Many aerobic and anaerobic bacteria are potential sources of these lipids which sometimes complicates the use of these biomarkers as proxies for ecological and environmental changes. Therefore, we applied preserved 16S ribosomal RNA genes to identify likely Holocene biological sources of bacteriohopanepolyols (BHPs) in the sulfidic sediments of the permanently stratified postglacial Ace Lake, Antarctica. A suite of intact BHPs were identified, which revealed a variety of structural forms whose composition differed through the sediment core reflecting changes in bacterial populations induced by large changes in lake salinity. Stable isotopic compositions of the hopanols formed from periodic acid-cleaved BHPs, showed that some were substantially depleted in 13C, indicative of their methanotrophic origin. Using sensitive molecular tools, we found that Type I and II methanotrophic bacteria (respectively Methylomonas and Methylocystis) were unique to the oldest lacustrine sediments (> 9400 years BP), but quantification of fossil DNA revealed that the Type I methanotrophs, including methanotrophs related to methanotrophic gill symbionts of deep-sea cold-seep mussels, were the main precursors of the 35-amino BHPs (i.e. aminopentol, -tetrol and -triols). After isolation of the lake ~3000 years ago, one Type I methanotroph of the 'methanotrophic gill symbionts cluster' remained the most obvious source of aminotetrol and -triol. We, furthermore, identified a Synechococcus phylotype related to pelagic freshwater strains in the oldest lacustrine sediments as a putative source of 2-methylbacteriohopanetetrol (2-Me BHT). This combined application of advanced geochemical and paleogenomical tools further refined our knowledge about Holocene biogeochemical processes in Ace Lake. © 2008 The Authors.